Gamma-glutamyl transferase to high-density lipoprotein cholesterol ratio has a non-linear association with non-alcoholic fatty liver disease: A secondary prospective cohort study in non-obese Chinese adults - Li, Qiming; Han, Yong; Hu, Haofei; Zhuge, Yuzheng (Frontiers in Medicine, 2022)
Objective: The evidence for a relationship between the ratio of gamma-glutamyl transferase (GGT) to high-density lipoprotein cholesterol (HDL-c) and non-alcoholic fatty liver disease (NAFLD) is currently inadequate. This study aimed to investigate the relationship between the GGT/HDL-c ratio and NAFLD. Methods: This study is a prospective cohort study that recruited a total of 11891 non-obese volunteers in a Chinese hospital from January 2010 to December 2014 in a non-selective manner. The Cox proportional-hazards regression model was then used to investigate the relationship between baseline GGT/HDL-c ratio and the probability of developing NAFLD. The non-linear link between the GGT/HDL-c ratio and NAFLD was identified using a Cox proportional hazards regression with cubic spline functions and smooth curve fitting (cubic spline smoothing). Furthermore, we conducted several sensitivity and subgroup analyses. Data had been uploaded to the DATADRYAD website. Results: The mean age of study participants was 43.29 ± 14.95 years old, and 6502 (54.68%) were male. The median (interquartile ranges) of GGT/HDL-c ratio was 15.56 (10.73-23.84). During a median follow-up of 29.35 months, 2028 (17.05%) participants were diagnosed with NAFLD. After adjusting for covariates, the results showed that GGT/HDL-c ratio was positively associated with incident NAFLD (HR = 1.014, 95%CI 1.011-1.017). There was also a non-linear relationship between GGT/HDL-c ratio and NAFLD, and the inflection point of the GGT/HDL-c ratio was 20.35. The effect sizes (HR) on the left and right sides of the inflection point were 1.113 (95%CI 1.096, 1.130) and 1.003 (95% CI 1.000-1.007), respectively. Moreover, the sensitivity analysis demonstrated the robustness of our results. Subgroup analysis showed that GGT/HDL-c ratio was more strongly associated with incident NAFLD in triglyceride (TG) <1.7 mmol/L participants. In contrast, the weaker association was probed in those with TG ≥1.7 mmol/L. Conclusion: The present study reveals a positive and non-linear relationship between the GGT/HDL-c ratio and NAFLD risk in a non-obese Chinese population. GGT/HDL-c ratio is strongly associated with NAFLD when GGT/HDL-c ratio is less than 20.35. Therefore, maintaining the GGT/HDL-c ratio lower than the inflection point is recommended from a treatment perspective.